Rasgos de personalidad y adicción al internet en los adolescentes de primero de bachillerato de una Unidad Educativa del Cantón Paltas, período 2022 - Gualán Requelme, Erika Enith (2023)
It is presumed that approximately a quarter of the population consists of people who go through the stage of adolescence, period in which the individual is in the process of development, where it reaffirms its personality. However, being exposed to positive or negative stimuli causes it to become a stage of greater vulnerability. Thus, the purpose of this research reveals whether personality traits are related to internet addiction in high school teenagers of an Educational Unit of Paltas Canton corresponding to the period April - September 2022. The methodology of this study has a quantitative approach, nonexperimental cross-sectional cohort design, descriptive and correlative type because it was possible to analyze and examine data from the two variables, the same ones that were collected over a period of time on a population of 62 students by intentional nonprobabilistic sampling, using selection criteria that allowed the use of the following assessment instruments, Millon Adolescent Clinical Inventory and the Questionnaire for Internet Addiction. The results showed that there is no statistically significant relationship between the two study variables, the predominant personality trait in this age group is the egocentric, followed by the rebellious and submissive trait; similarly, it was evident that adolescents did not present internet addiction. Finally, this work allowed the design of a plan of promotion and prevention, aimed at providing tools and strategies that allow adolescents to take care of and promote their mental health and thus avoid excessive use of the internet